2014
DOI: 10.1093/aepp/ppu040
|View full text |Cite
|
Sign up to set email alerts
|

Crop Prices, Agricultural Revenues, and the Rural Economy1

Abstract: U.S. policy makers often justify agricultural subsidies by stressing that agriculture is the engine of the rural economy. We use the increase in crop prices in the late 2000s to estimate the marginal effect of increased agricultural revenues on local economies in the U.S. Heartland. We find that $1 more in crop revenue generated 64 cents in personal income, with most going to farm proprietors and workers (59 percent) or nonfarmers who own farm assets (36 percent). The evidence suggests a weak link between reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This results in a high proportion of farmers growing the same crop, regardless of local environmental conditions (e.g., soils, water availability, climate), which drives prices down and limits profits. Weber et al (2015) argued that the current subsidy structure negatively affects huge sections of rural communities as these subsidies provide little benefit to anyone other than the direct benefits to the farmers. Similarly, Reimer and Weerasooriya (2019) found that the Farm Bill has an overall positive effect on agricultural prices, but the entire effect is due to the nutrition component (i.e., Supplemental Nutrition Assistance Program; SNAP) as farm subsidies actually depress agricultural prices and have an overall net negative impact on U.S. economic output.…”
Section: Discussionmentioning
confidence: 99%
“…This results in a high proportion of farmers growing the same crop, regardless of local environmental conditions (e.g., soils, water availability, climate), which drives prices down and limits profits. Weber et al (2015) argued that the current subsidy structure negatively affects huge sections of rural communities as these subsidies provide little benefit to anyone other than the direct benefits to the farmers. Similarly, Reimer and Weerasooriya (2019) found that the Farm Bill has an overall positive effect on agricultural prices, but the entire effect is due to the nutrition component (i.e., Supplemental Nutrition Assistance Program; SNAP) as farm subsidies actually depress agricultural prices and have an overall net negative impact on U.S. economic output.…”
Section: Discussionmentioning
confidence: 99%
“…Under our empirical specification, these regulatory changes thus arguably provide exogenous variation to agricultural wages. Further, many empirical studies have shown that the farm economy has a negligible impact at most on nonfarm sectors, that is, Foster and Rosenzweig (2004), Hornbeck and Keskin (2014), and Weber et al (2015). Our analysis covers 2006–2018, which incorporates years before and after major increase in minimum wage around 2014–2015.…”
Section: Introductionmentioning
confidence: 99%
“…Whether agricultural activity creates meaningful short run economic spillovers remains an open question. However, the literature finds little to no evidence of long-run economic spillovers from the agricultural sector to other local non-farm sectors (Foster & Rosenzweig, 2004;Hornbeck & Keskin, 2015;Weber et al, 2015) 7 Whereas well acquainted neighbors with established friendships are more likely to keep a watchful eye on their neighbor's house, they may be less likely to recognize an ongoing burglary at a stranger's house. Relatedly, committing a crime in an environment of strong social organization is especially risky as witnesses are more likely to recognize the perpetrator's face and identify them to police.…”
mentioning
confidence: 99%